REFLEKSI PENCIPTAAN MANUSIA BERBANGSA-BANGSA DAN BERSUKU-SUKU (TELAAH SURAH AL-HUJURÃ‚T AYAT 13) - AM, Mirhan (Faculty of Ushuluddin and Humanities, 2015)
In the uniqueness and the various of creating of human covered by Allah The almighty, we can take a study about the relationship between the Quran exegesis and the creating of human, then it reveals the differences of quality between one social community and the others according to their group. Islam with Quran argumentation only sees and values of people based on their piety to The God, Allah, not from the body shape, colour of skin, superiority of certain nation, the language, culture and custom, and other social regulation.